Integration Of Character and Moral Education of Students in Christian Education - Esti Regina Boiliu (International Journal of Christian Education and Philosophical Inquiry, 2025)
Character and moral education are essential pillars in shaping the personality of Christian students, especially in the context of the disruptive era, which is increasingly marked by rapid technological advancement, moral degradation, and shifting social values. The rise of digitalization and modernization presents new challenges to students' moral integrity, empathy, and spiritual grounding. This article aims to explore and analyze the strategic role of Christian Education in addressing these challenges by integrating character and moral education rooted in Christian values. Using a qualitative literature review method, this study draws from a wide range of primary and secondary sources that include theories of character education, moral development, and biblical-Christian perspectives. The findings indicate that a holistic approach to Christian Education—one that incorporates moral instruction, spiritual formation, and practical application through discipleship, prayer, and the example of Christian educators—can significantly contribute to students’ character development. Furthermore, this integration cultivates not only moral awareness and social responsibility but also fosters resilience and faith-based identity formation. The article also proposes a contextual model for character and moral education that aligns with the demands of the disruptive era, emphasizing the importance of spiritual values alongside intellectual growth. This model serves as a framework for educators to nurture morally and spiritually grounded individuals capable of navigating complex social realities with integrity and compassion. In conclusion, Christian Education, when grounded in strong theological and pedagogical foundations, has the transformative potential to shape a generation of students who are not only academically competent but also morally upright and spiritually mature